Mindfulness's moderating role applied on online SEL education - Ho, Chun-Heng; Zhang, Hang-qin; Li, Juan; Liu, An'an (Frontiers in Psychology, 2024)
Introduction Mild to moderate depression, anxiety, and stress imbalances are prevalent emotional issues among college students and are primary factors leading to deficiencies in social-emotional skills within this population. Without timely intervention, these mild to moderate emotional issues may escalate into more severe conditions. Social-Emotional Learning (SEL) programs are effective for building social-emotional skills. However, current research on SEL programs has not adequately addressed the issue of high-quality teacher-student interactions for students who suffer emotional problems. To tackle this issue, this study proposes a curriculum approach that integrates mindfulness with rhythmic music? and evaluated the emotional changes of students after mindfulness with rhythmic music curriculum. Methods This study adopted a pre-post experimental design. Two hundred and ninety-four firefighting universities students participated in a one-semester “online mindfulness combined with music rhythm SEL course”. The study used the Beck Anxiety Inventory, Center for Epidemiologic Studies Depression Scale and Perceived Stress Scale to measure the anxiety, depression and stress levels of the participants before and after the course, and used the participants' self-reflection reports as a method to explore the students' emotional transformation patterns. Results The research findings indicate that: (1) eighth-note, quarter-note, and sixteenth-note rhythmic music significantly improve the emotional wellbeing of students with depression, anxiety, and stress imbalances, respectively. (2) The degree of emotional improvement has a certain impact on academic performance. (3) Students with anxiety require more instructional support focused on attention concentration during the early phases of the course; students with depression should not be scheduled for social skills learning modules in the short term and need long-term instructional guidance; individuals experiencing stress imbalances require attention to their personal music preferences and benefit from additional listening activities and exercise. Discussion These findings assist teachers in accurately identifying emotional changes among students with emotional problems and managing the patterns of these emotional transitions, thereby providing effective instructional support and promoting high-quality interactions between teachers and students.